LANGSTON HUGHES AND HIS POETRY - Roziboyeva Ra’no; Eldorbek Erkinovich Hamitov (Ta'lim innovatsiyasi va integratsiyasi, 2024)
This article delves into the enduring legacy of Langston Hughes, one of the most influential figures in American literary history. Focusing primarily on his poetic works, the analysis examines Hughes's exploration of themes such as race, identity, and the American Dream. By delving into the socio-political context of his time and the impact of the Harlem Renaissance, the article highlights Hughes's unique ability to capture the essence of the African American experience through his evocative verse. Through a close reading and select poems, including "The Negro Speaks of Rivers" and "Harlem," the article elucidates Hughes's mastery of language and his commitment to social justice. Furthermore, it explores how Hughes's poetry continues to resonate with readers today, inspiring new generations to confront issues of inequality and pursue dreams of equality and freedom.